2008
DOI: 10.1007/s00134-008-1122-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perioperative atelectasis on antibiotic penetration into lung tissue: an in vivo microdialysis study

Abstract: Data indicate that postoperative interstitial antibiotic concentration is influenced by perioperative atelectasis formation. Our findings suggest the re-evaluation of clinical dosing schemas of antibiotic therapy in a variety of diseases associated with atelectasis formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Improvements in the methodology used to sample ELF drug concentrations have addressed known limitations of the technique (144), namely, the inaccuracies associated with quantifying the ELF volume and the inability to sample the same site multiple times (145). Microdialysis has also been applied as a means to quantify lung concentrations of antimicrobials in human subjects (83,85,94,142,146,147). However, a limitation of the technique in this setting is that pulmonary infections may be located in different compartments (e.g., alveoli, bronchioles, and intracellularly) (148).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Improvements in the methodology used to sample ELF drug concentrations have addressed known limitations of the technique (144), namely, the inaccuracies associated with quantifying the ELF volume and the inability to sample the same site multiple times (145). Microdialysis has also been applied as a means to quantify lung concentrations of antimicrobials in human subjects (83,85,94,142,146,147). However, a limitation of the technique in this setting is that pulmonary infections may be located in different compartments (e.g., alveoli, bronchioles, and intracellularly) (148).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Data from that study showed that LVX concentrations in lung tissue were significantly higher in patients undergoing coronary artery bypass grafting with OPCAB than in patients operated on with CPB (10), suggesting that extracorporeal circulation affects antibiotic distribution into lung tissue. However, the limitation of our previous in vivo microdialysis study (10) in humans was the localization of microdialysis probes in lung tissue. Surgical access permitted insertion of microdialysis probes for intrapulmonary measurements of LVX concentrations in ventrally sited lung areas only.…”
Section: Discussionmentioning
confidence: 96%
“…Previous data from our study group showed that levofloxacin (LVX) concentrations in lung tissue were significantly higher in patients undergoing OPCAB than in patients undergoing surgery with CPB (10), suggesting that the ventilation-perfusion mismatch after CPB affects antibiotic distribution into lung tissue.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Because ventilation/perfusion mismatch due to atelectasis may also influence antibiotic distribution to lung tissue, hence increasing the risk of post-operative pneumonia, Hutschala et al compared the penetration of levofloxacin into the lung of two groups of patients, using microdialysis probes to sequentially determine in vivo lung tissue levels. The first group consisted of five patients who underwent coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB) (atelectasis model), and the second one, of five patients operated with the offpump coronary artery bypass grafting (OPCAB)-technique [74]. In the OPCAB-group, the median of the maximum concentration of levofloxacin in lung tissue was significantly higher compared with the CPB-group, establishing that atelectasis formations lead to critically lower lung tissue concentrations of levofloxacin in nondependent parts of lung tissue.…”
Section: Advances In Treatmentmentioning
confidence: 99%